HCAR2 Exerts Anti-Depressive Effects on Corticosterone-Induced Depression in Mice by Modulating Microglial Activity - Zhao Pan; Li Jiang; Jiacheng Chen; Sicong Xu; Ping Zhang; Yili Yi; Yangzhi Xie; Yongjun Chen (Frontiers in Bioscience-Landmark)
Background: The metabolites derived from judicious dietary choices play a crucial role in the management and treatment of depression. Hydroxy-carboxylic acid receptor 2 (HCAR2) functions as a receptor for various diet-derived metabolites. Although a growing body of evidence indicates these metabolites exert beneficial effects on depression, the precise mechanisms underlying these benefits require further investigation. Methods: We established a mouse model of corticosterone (Cor)-induced depression to evaluate the therapeutic potential of HCAR2 activation on depression. A series of behavioral experiments were conducted to investigate whether HCAR2 activation could alleviate depressive-like behaviors in mice. The neuroprotective effects of HCAR2 in the hippocampus were examined using Nissl and hematoxylin-eosin (HE) staining. The levels of monoamine neurotransmitters in mouse serum were quantified, as well as the cell viability and lactate dehydrogenase (LDH) activity of hippocampal neurons co-cultured with primary microglia. Microglia-associated neuroinflammation was evaluated by quantifying pro-inflammatory cytokines using ELISA, and by assessing the polarization state of M1 microglia, including the mRNA expression levels of M1 markers and double fluorescence staining for inducible nitric oxide synthase/ionized calcium-binding adapter molecule 1 (iNOS/Iba1). The expression level of proteins in the protein kinase B-inhibitor of nuclear factor kappa-B kinase subunits alpha and beta-nuclear factor kappa-light-chain-enhancer of activated B cells (AKT-IKKαβ-NFκB) pathway in primary microglia was analyzed using western blot. Transcriptomic changes in microglia induced by HCAR2 activation were examined through RNA sequencing. Mice were fed PLX5622 chow to deplete microglia in vivo. Results: Activation of HCAR2 by its agonist MK-6892 in a Cor-induced model of depression significantly alleviated depressive-like behaviors, attenuated hippocampal neuronal injury, increased serum monoamine levels, reduced microglia-associated neuroinflammation, and inhibited the expression of proteins in the AKT-IKKαβ-NFκB pathway in primary microglia. Additionally, HCAR2 activation markedly enhanced hippocampal neuronal viability and decreased LDH activity in this co-culture system. Importantly, these protective effects were abolished in HCAR2 knockout mice. RNA sequencing revealed that HCAR2 activation induced changes in multiple signaling pathways. Moreover, the depletion of microglia also eliminated the protective effects of MK-6892. Conclusion: Activation of HCAR2 can reduce depressive-like behaviors, neuronal injury, and neuroinflammation. Our findings suggest these neuroprotective effects are, at least in part, mediated through modulation of microglial activity by HCAR2.